Size and the Growth of Firms - Samuels, J. M. (Review of Economic Studies, 1965)
Journal Article Size and The Growth of Firms Get access J. M. Samuels J. M. Samuels University of Birmingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 2, April 1965, Pages 105–112, https://doi.org/10.2307/2296055 Published: 01 April 1965